Rede política no arranjo produtivo local calçadista de Jaú - Malagolli, Guilherme Augusto (2011)
The policy network is regarded as a relatively stable set of relationships that are not hierarchical and that have an interdependent nature linking a variety of actors who share common interests with regard to a policy and who exchange resources to pursue those shared interests, recognizing that cooperation is the best way to achieve common goals. The study of policy network is crucial to understanding the environment in which there is strategic interaction of actors and organizations that are dependent upon various resources, such as financial, technological, organizational, political, legal and constitutional. The implementation of the study network policies in Clusters (APLs) can explain the economic and social development planning, through the formulation of policies adopted locally. This paper aims to analyze the existence and configuration of the APL Policy Network of women's shoes Jau economic transactions around the actors. So is it possible to identify the central actors of the network policy and show how network structure influences the policy of Local Governance, which can facilitate economic transactions of the actors. For this, we made a field survey, using a semi-structured questionnaire with companies, unions and representatives of local government in APL footwear Jau.